MASA KEJAYAAN ISLAM Kajian Terhadap Aktualisasi Nilai-nilai Keimanan dalam Ajaran Islam dan Pengaruhnya terhadap Perkembangan Keilmuan - Masduki, Masduki (EDUKASI: Jurnal Pendidikan Islam, 2015)
In contrast to Western civilization are experiencing stagnation and deterioration due to dogmatism confined religion, Islamic civilization actually progressed in the spirit of actualizing the values of faith. In other words, Islamic civilization and Western civilization has a different experience in terms of the role of religion in encouraging the advancement of civilization. In its heyday, Islamic civilization and contribute a big share in building a world civilization and eventually also lead to the development of civilization barat.Tulisan culture is going to elaborate on the contribution of Islamic civilization to the development of science globally. This effort is conducted not in the romance of history that is apologetis.but more than that, this effort made to develop the rekindling the spirit of Islamic culture and civilization through the messages of Islam. Thus sacred teachings, in the hopes the spirit of actualizing the values of faith are ever advancing civilization Islam in the past to spur the development of science and Islamic civilization today.